2016
DOI: 10.1017/s0714980816000209
|View full text |Cite
|
Sign up to set email alerts
|

Best-Practice Guideline on the Prevention of Abuse and Neglect of Older Adults

Abstract: RÉSUMÉUne revue systématique de la littérature a été effectuée afi n d'identifi er des moyens effi caces pour prévenir et combattre l'abus et la négligence envers les adultes âgés dans les établissements de soins de santé au Canada. L'examen a été fait en utilisant les bases de données qui ont été recherchés à partir de janvier 2000 à avril / mai 2013. En outre, les membres des groupes d'experts ont présenté les citations d'articles tirés des archives personnelles. Deux associés de recherche infi rmier (ARI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 67 publications
0
35
0
3
Order By: Relevance
“…Caregiver emotional distress measured on scale from 0 (not at all) to 5 (extremely).Caregivers need training to help reduce caregiving burden which can contribute to elder abuse.Hirst/October 2015 [25]Defining what is known about resident-to-resident abuse and what gerontological nurses can do about the widespread problem.Residents in long-term care facilities.Collecting a body of research literature regarding aggression and violence between long-term care residents.Previous research and literature.Resident-to-resident abuse is more prevalent than staff-to-resident abuse, but it is researched much less.RRA tends to target those residents with cognitive impairment.Staff needs to be educated on RRA to facilitate recognition. Guidelines should be provided to staff when RRA occurs.Ensure accurate and complete documentation to facilitate reporting.Aggression and violence between long-term care residents has been largely overlooked by researchers.Hirst/August 2015 [26]To identify effective approaches to preventing and addressing abuse and neglect of older adults within health care settings.62 studies focusing on identifying, assessing, and responding to abuse and neglect of older adults.Systematic review of literature and submittal of article citations from expert panel members. Additionally, screening of literature for inclusion and reliability.Expert panel and guided questions to determine appropriate study selection and data sources.“Abuse and neglect of older adults remains under-explored.”Abuse and neglect of older adults is more likely more prevalent than reported.There exists a knowledge and training deficit around the abuse and neglect of older adults.The continued culture of de-valuing older adults will continue to allow these older adults to remain highly susceptible to all forms of abuse.Dempsey/March 2015 [27]There should be improvements to enhance a person’s quality of life with dignity in an appropriate setting of palliative care.Dementia patients in a clinical setting.Advanced planning to the specific care of the diseases.Training to clinical staff.People with dementia often do not receive the palliative care as do other terminally ill patients.Ferrah/January 2015 [28]To examine the published research on the frequency, nature, contributing factors, and outcomes of RRA in nursing homes.Studies and data from articles related to older adults.This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Key terms were reviewed independently by each researcher.RRA is ubiquitous with serious consequences for residents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiver emotional distress measured on scale from 0 (not at all) to 5 (extremely).Caregivers need training to help reduce caregiving burden which can contribute to elder abuse.Hirst/October 2015 [25]Defining what is known about resident-to-resident abuse and what gerontological nurses can do about the widespread problem.Residents in long-term care facilities.Collecting a body of research literature regarding aggression and violence between long-term care residents.Previous research and literature.Resident-to-resident abuse is more prevalent than staff-to-resident abuse, but it is researched much less.RRA tends to target those residents with cognitive impairment.Staff needs to be educated on RRA to facilitate recognition. Guidelines should be provided to staff when RRA occurs.Ensure accurate and complete documentation to facilitate reporting.Aggression and violence between long-term care residents has been largely overlooked by researchers.Hirst/August 2015 [26]To identify effective approaches to preventing and addressing abuse and neglect of older adults within health care settings.62 studies focusing on identifying, assessing, and responding to abuse and neglect of older adults.Systematic review of literature and submittal of article citations from expert panel members. Additionally, screening of literature for inclusion and reliability.Expert panel and guided questions to determine appropriate study selection and data sources.“Abuse and neglect of older adults remains under-explored.”Abuse and neglect of older adults is more likely more prevalent than reported.There exists a knowledge and training deficit around the abuse and neglect of older adults.The continued culture of de-valuing older adults will continue to allow these older adults to remain highly susceptible to all forms of abuse.Dempsey/March 2015 [27]There should be improvements to enhance a person’s quality of life with dignity in an appropriate setting of palliative care.Dementia patients in a clinical setting.Advanced planning to the specific care of the diseases.Training to clinical staff.People with dementia often do not receive the palliative care as do other terminally ill patients.Ferrah/January 2015 [28]To examine the published research on the frequency, nature, contributing factors, and outcomes of RRA in nursing homes.Studies and data from articles related to older adults.This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.Key terms were reviewed independently by each researcher.RRA is ubiquitous with serious consequences for residents.…”
Section: Resultsmentioning
confidence: 99%
“…The theme most often mentioned was policies/programs; identified in 24/64 of total occurrences (41%) 13,14,17,20–23,26,28,29,32,34,36,38,41. Policies/programs refer to the implementation of any new type of company policy or any program initiated within the facility or by local or federal means intended to enable the ability to reduce abuse of residents with either dementia or Alzheimer’s 13,20,26,36. Administrators should have an open-door policy to allow residents and family members to discuss issues freely, including any potential abuse by staff members 13.…”
Section: Resultsmentioning
confidence: 99%
“…Studier fra USA (Pillemer & Moore, 1989), Canada (Hirst, 2002), Sverige (Saveman, Åstrøm, Bucht & Norberg, 1999), Finland (Isola, Backman, Voutilainen & Rautsiala, 2003), Tyskland (Goergen, 2001) og Irland (Drennan et al, 2012) har vist at sykehjemsansatte har både observert handlinger av utilstrekkelig omsorg og selv innrømmet å begå slike handlinger. De hyppigst observerte handlingene har vaert forsømmelser og handlinger av psykisk karakter.…”
Section: Hva Er Vold Overgrep Og Forsømmelser?unclassified
“…De hyppigst observerte handlingene har vaert forsømmelser og handlinger av psykisk karakter. De er ofte relatert til omsorgsaktiviteter, som at en forlater en beboer alene eller unnlater å skifte bleie (Isola et al, 2003), at en med vilje overser eller avviser en beboer (Drennan et al, 2012), at en fysisk tar tak i en beboer utover det som er nødvendig (Drennan et al, 2012), eller at en ikke tilstrekkelig setter i verk forebyggende tiltak for å hindre trykksår hos sengeliggende beboere (Goergen, 2001).…”
Section: Hva Er Vold Overgrep Og Forsømmelser?unclassified
“…Programs to combat elder mistreatment have been developed and implemented for more than three decades, and many vulnerable older adults, as well as families and professionals who serve them, have benefitted. Despite this, previous systematic literature reviews examining programs have found few that systematically analyzed outcomes and even fewer that demonstrated measurable impact. This is partly because of the complexity of designing and evaluating elder mistreatment programs and because the relatively young field includes collaborative teams with various levels of funding and research sophistication.…”
mentioning
confidence: 99%